ENVIRONMENTAL PROTECTION DEDUCTIONS AND INSURANCE OF OBJECTS OF SUBSOIL USE (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
In the article questions related to payments for environmental protection measures, re-cultivation and mine closure were discussed. The need of bringing them in accordance with international standards was marked. The problems of sanitary protection zones and liability insurance of activities of mining companies were touched up.
Keywords: mining industry; mining company; sanitary-protection zone; liability and responsibility insurance; re-cultivation and conservation of mine